A hybrid stochastic/deterministic unit commitment based on projected disjunctive MILP reformulation - Tan, W. S. (Institute of Electrical and Electronics Engineers Inc., 2016)
This letter presents a new expression of the chance constraint, representing ramping and operating reserve, in the context of the mixed integer linear programming (MILP) formulation for solving the hybrid stochastic/deterministic unit commitment (SDUC) problem. Based on projected disjunctive programming, the nonlinear chance constraint is converted into a set of linear constraints that has a more compact size. Numerical simulations highlight the primacy of the proposed MILP-SDUC reformulation as compared with other formulation approaches.